Influence of Substrate in Roll-to-roll Coated Nanographite Electrodes for Metal-free Supercapacitors - Blomquist, Nicklas (Sci Rep, 2020)
Due to the high electric conductivity and large surface area of nanographites, such as graphene and graphite nanoplatlets, these materials have gained a large interest for use in energy storage devices. However, due to the thin flake geometry, the viscosity of aqueous suspensions containing these materials is high even at low solids contents. This together with the use of high viscosity bio-based binders makes it challenging to coat in a roll-to-roll process with sufficient coating thickness. Electrode materials for commercial energy storage devices are often suspended by organic solvents at high solids contents and coated onto metal foils used as current-collectors. Another interesting approach is to coat the electrode onto the separator, to enable large-scale production of flat cell stacks. Here, we demonstrate an alternative, water-based approach that utilize slot-die coating to coat aqueous nanographite suspension with nanocellulose binder onto the paper separator, and onto the current collector as reference, in aqueous metal-free supercapacitors. The results show that the difference in device equivalent series resistance (ESR) due to interfacial resistance between electrode and current collector was much lower than expected and thus similar or lower compared to other studies with a aqueous supercapacitors. This indicates that electrode coated paper separator substrates could be a promising approach and a possible route for manufacturing of low-cost, environmentally friendly and metal-free energy storage devices.